POLYLACTIC ACID (PLA) SCAFFOLD FOR CONTROLLED RELEASE OF ESSENTIAL OIL OF CANELO DRIMYS WINTERI: CONTROL OF PHYTOPATHOGENS IN FRUITS - Duran, Christian Nuñez; Cabrera-Pardo, Jaime; Ahumada, Ramon; GUZMÁN, CATHERINE; Méndez , Paola; Peña-Farfal, Carlos; Maureira, Antonio; Nova, Manuel; Romero-Villegas, Enzo; González del Pino, Sergio; Nuñez-Duran, Artemisa; Novoa, Vanessa (Journal of the Chilean Chemical Society, 2025)
We have designed and prepared polylactic acid (PLA)-based porous support for the controlled release of essential oils from Drimys winteri, common name Canelo (CEO). The chemical composition of the essential oil was characterized by HS/GC-MS. The interaction with the PLA-based porous support was determined by FTIR-ATR spectrophotometry. Our results showed that the manufactured PLA support allows the controlled release of essential oils over time, at 21 °C. The PLA/essential oil support showed a non-contact antifungal activity against B. cinerea. In addition, pure compounds (standards) detected in the gas phase of CEO essential oil were independently studied to identify which of these molecules is responsible for the growth control action of the fungus. In conclusion, the PLA/CEO porous support is an alternative to protect against infections such as B. cinerea, offering a potential use of this strategy to preserve fresh functional foods in the post-harvest stage, as an atmosphere modifier.